Predicting Emissions of SVOCs from Polymeric Materials and Their Interaction with Airborne Particles - Xu, Ying; Little, John C (Environmental science & technology, 2006)
A model that predicts the emission rate of volatile organic compounds (VOCs) from building materials is extended and used to predict the emission rate of semivolatile organic compounds (SVOCs) from polymeric materials. Reasonable agreement between model predictions and gas-phase di-2-ethylhexyl phthalate (DEHP) concentrations is achieved using data collected in a previous experimental study that measured emissions of DEHP from vinyl flooring in two very different chambers. While emissions of highly volatile VOCs are subject to “internal” control (the material-phase diffusion coefficient), emissions of the very low volatility SVOCs are subject to “external” control (partitioning into the gas phase, the convective mass-transfer coefficient, and adsorption onto interior surfaces). The effect of SVOCs partitioning onto airborne particles is also examined. The DEHP emission rate is increased when the gas-phase concentration is high, and especially when partitioning to the airborne particles is strong. Airborne particles may play an important role in inhalation exposure as well as in transporting SVOCs well beyond the source. Although more rigorous validation is needed, the model should help elucidate the mechanisms governing emissions of phthalate plasticizers, brominated flame retardants, biocides, and other SVOCs from a wide range of building materials and consumer products.